Analysis of the Influence of the Implementation of Good Corporate Governance on the Financial Performance of the Company - Andi Mahdiana Mardatillah; Muhammad Ali; Fauzi R Rahim (Jurnal Office, 2023)
Good Corporate Governance is a series of processes that can affect the direction, management and control of a company or corporation. The purpose of this study is to determine the extent to which the effect of the implementation of Good Corporate Governance on financial performance in companies, Bankruptcy measurement of a company can be measured through financial reports in the company, financial reports are a source of information that can concurrently provide information about corporate value. The impact of Good Corporate Governance can regulate the company's internal processes and can improve company performance, and make it easier to obtain cheaper financing funds which will ultimately increase corporate value. , This article was prepared based on data and references obtained from scientific journals related to the discussion. This study uses literature which has been used as a reference source for this article, in the literature review using primary sources and secondary sources. corporate governance has a positive effect on return on equity, and there is no positive relationship between good corporate governance and Tobin's Q. In this case, it shows that the implementation of good corporate governance influences operational performance and profit achievement. companies but the market response to the implementation of good corporate governance is still lacking.